ANTAGONISM OF Trichoderma SPECIES AGAINST PLANT PATHOGENS CAUSING ROOT ROT OF PEPPER - Torres-Torres, Edel; Guigón-López, César; Uranga-Valencia, Luisa Patricia; Guerrero-Morales, Sergio (Ecosistemas y Recursos Agropecuarios, 2024)
The pepper crop has a high production value in Mexico and isone of the main horticultural products. Wilt is the main crop disease, caused by the phytopathogens Rhizoctonia solani, Fusarium spp. and Phytophthora capsici. The management of the disease is unsatisfactory to date, therefore, the objective of this research was to evaluate the in vitro antagonistic capacity of native isolates of Trichoderma asperellum, T. yunnanense, T. brevicompactum and T. simmonsii against the three agents that cause root rot. In the laboratory, the growth of each phytopathogen was determined when they were placed in dual confrontation, in soluble compounds (SC) assay by the cellophane film method and in volatile organic compounds (VOC) assay. The statistical analysis indicated that, in direct confrontation the four species more inhibited R. solani (52 to 75%) and P. capsici (64 to 69%); to Fusarium sp, only from 19 to 47%. The CS of T. brevicompactum inhibited R. solani by 64%. T. simmonsii CS inhibited P. capsici by 34%. The VOCs produced by T. yunnanense affect the growth of R. solani by more than 60%. Those of T. simmonsii and T. brevicompactum mostly to P. capsici (34-35%). The participation of CS and VOCs in the inhibition varies depending on the Trichoderma species and the phytopathogenic species. Finally, native biocontrol species have the potential to become a solution alternative for root rots of pepper.